2008
DOI: 10.1186/1744-8069-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of TRPV1 on Diabetes-Induced Alterations in Thermal Pain Sensitivity

Abstract: A common complication associated with diabetes is painful or painless diabetic peripheral neuropathy (DPN). The mechanisms and determinants responsible for these peripheral neuropathies are poorly understood. Using both streptozotocin (STZ)-induced and transgene-mediated murine models of type 1 diabetes (T1D), we demonstrate that Transient Receptor Potential Vanilloid 1 (TRPV1) expression varies with the neuropathic phenotype. We have found that both STZ- and transgene-mediated T1D are associated with two dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
107
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 66 publications
9
107
0
2
Order By: Relevance
“…Our present data do not allow further speculation on this issue. However, since the spinal production of TRPV1 has been correlated with the development of thermal hyperalgesia in diabetic animals [5,29], our data underline the possibility that the efficacy of electroacupuncture in the control of spinal sensitisation during the development of neuropathic pain states could be mediated by the modulation of NGF and TRPV1 levels.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our present data do not allow further speculation on this issue. However, since the spinal production of TRPV1 has been correlated with the development of thermal hyperalgesia in diabetic animals [5,29], our data underline the possibility that the efficacy of electroacupuncture in the control of spinal sensitisation during the development of neuropathic pain states could be mediated by the modulation of NGF and TRPV1 levels.…”
Section: Discussionmentioning
confidence: 82%
“…Painful neuropathy is associated with behavioural manifestations of sensory dysfunctions, and neurochemical alterations of biological mediators in the peripheral nervous system [2]. In particular, alterations in the content of neurotrophin nerve growth factor (NGF) in tissues (skin, muscle and serum) [3] are associated with spinal variations in substance P (SP) [3] and transient receptor potential vanilloid 1 (TRPV1) receptor [4,5]. These latter are known to be under the control of NGF [6][7][8] and have been related to diabetes-induced neuropathy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DD04107 Ameliorated the Mechanical Sensitivity of a Diabetic Neuropathy. We also investigated the effect of the peptide on the mechanical allodynia associated to a diabetes-induced neuropathy (Pabbidi et al, 2008;Suri and Szallasi, 2008). Administration of STZ into mice increases the plasma glucose levels above 250 mg/dl, producing overtime a peripheral neuropathy exhibiting conspicuous mechanical hypersensitivity (Fig.…”
Section: Dd04107 Reduced the Thermal Hyperalgesia And Mechanical Allomentioning
confidence: 99%
“…10 A recent report suggested that TRPV1 expression is altered in the streptozotocin-induced and transgene-mediated type-1 diabetes mouse model. 31 Thus, it is suggested that pruritus signals were blocked not only by damaged C-fibers, but also by reduced expression of receptors.…”
Section: Discussionmentioning
confidence: 99%